Pandangan Negatif terhadap Diri pada Lansia dan Faktor yang Memengaruhinya: Systematic Literature Review - Flory Aura Najla; Dinda Mulan Aulia; Ludfiah Azahra; Rahmadianti Aulia (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Negative self-perceptions among older adults represent a form of internalized ageism that may adversely affect psychological well-being and quality of life. This study aimed to identify the forms of negative self-perceptions in older adults, the factors associated with their development, their psychological consequences, and potential interventions to address them. A Systematic Literature Review (SLR) was conducted following the PRISMA guidelines. Literature searches were performed in PubMed, ScienceDirect, and Sage Journals databases. Of the 97 records identified, 12 studies met the inclusion criteria and were included in the analysis. The findings revealed that negative self-perceptions among older adults commonly manifest as internalized ageist stereotypes, negative self-perceptions of aging, and self-directed ageism. Contributing factors include sociodemographic characteristics, physical and psychological health conditions, sociocultural environments, and experiences with healthcare services and social institutions. Negative self-perceptions were associated with adverse psychological outcomes, including increased depression, anxiety, and reduced engagement in health-promoting behaviors. Several intervention approaches were identified, including psychological programs targeting internalized ageism, physical activity interventions, meaningful activity engagement, and strategies aimed at improving age-inclusive healthcare practices and broader social policies. These findings highlight the need for multidimensional interventions at individual, social, and structural levels to promote healthier aging.